2021
DOI: 10.1177/10760296211063882
|View full text |Cite
|
Sign up to set email alerts
|

Medical Adjuvant Therapy in Reducing Thrombosis With Arteriovenous Grafts and Fistulae Use: A Meta-Analysis of Randomized Controlled Trials

Abstract: Hemodialysis is required for patients with end-stage renal disease (ESRD) that require arteriovenous (AV) grafts or fistulas for vascular access. These access points are prone to thrombosis. To determine the effect of medical adjuvant therapy on AV graft/fistula patency among patients with ESRD on hemodialysis. Adhering to the PRISMA 2020 statement, a systematic search was conducted until August 20, 2021, with keywords including arteriovenous graft, fistula, patency, thrombosis, hemodialysis, adjuvant treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The role of medications started perioperatively to prevent or improve flow-related arteriovenous access dysfunction remains unresolved despite a meta-analysis of 13 RCTs (1985 patients) . Older data of small short-term (<1 month) studies suggested ticlopidine may provide limited (<1 month) patency benefit for AVFs (10.5%-25.0% thrombosis in ticlopidine vs 47.1%-50.0% placebo); however, subsequent larger long-term RCTs have not been conducted to support this supposed advantage. For AVGs, aspirin-dipyridamole or fish oil may provide primary patency benefit and reduce the need for interventions to maintain patency for AVGs .…”
Section: Arteriovenous Access Complicationsmentioning
confidence: 99%
“…The role of medications started perioperatively to prevent or improve flow-related arteriovenous access dysfunction remains unresolved despite a meta-analysis of 13 RCTs (1985 patients) . Older data of small short-term (<1 month) studies suggested ticlopidine may provide limited (<1 month) patency benefit for AVFs (10.5%-25.0% thrombosis in ticlopidine vs 47.1%-50.0% placebo); however, subsequent larger long-term RCTs have not been conducted to support this supposed advantage. For AVGs, aspirin-dipyridamole or fish oil may provide primary patency benefit and reduce the need for interventions to maintain patency for AVGs .…”
Section: Arteriovenous Access Complicationsmentioning
confidence: 99%